Hidden hazardous child labor as a complex human rights phenomenon: A case study of child labor in Pakistan’s brick-making industry - Ali, Mohammad Abbas (Cogent social sciences, 2017)
We examine the phenomenon of child labor in conditions where child labor is hazardous, unpaid family work, and exists in local industries. The overriding purpose of this study is to develop theoretical generalizations that may help comprehend the causes of hidden hazardous child labor in similar conditions eventually leading to effective steps in eradicating or controlling it. We consider child labor as a basic human rights issue and, hence, investigate it as a complex social phenomenon by merging two academic perspectives, i.e. the subaltern tradition in history, and the economic theories of entitlement, capability and function as propounded by Prof. Amartya Sen. We have found that the kiln-workers are invisible to the society. Their marginal existence allows them minimal options for improvement leading to a sense of despondency that decimates their self-esteem to the point where they believe that their basic human rights are negotiable. We conclude that to ameliorate the conditions of the kiln-workers there is a need to create an environment in which they are given the capability to exercise their given legal, political, and economic rights. Finally, we conclude that such an environment can be created through a multi-stakeholders approach spearheaded by the government and supported by unions, and non-governmental organizations.